Penggunaan Komputer di Kalangan Guru-Guru Dalam Pengurusan Kurikulum di Sekolah Menengah Daerah Sik, Kedah - Mohamad Nabzrim, Mohamad Nayan (1997)
This study attempts to evaluate the use of computer in the curriculum management by the teachers in the national secondary schools. 41 teachers who are the Curriculum Committee Members involved in the study. The results showed that all schools are equipped with computer facilities. In addition, the teachers used the computers to keep the students’ records, stocks and inventories, preparing documents such as notes, timetabling, exam registration and analyzing, subjects panel filing management, etc. Besides that, Chi Square, T-test and ANOVA were used to analyze the relationship between the independent and the dependent variables. The tests revealed that there were statistically significant relationship in the teachers’ attitudes and computer training toward the use of computers. However, there was no significant relationship in computer literacy toward the computer use. Similarly, no significant differences in terms of sexes, ages and academic qualifications with the use of computers among the teachers. These results were obtained through questionaires and informal interview. The data collected through these techniques complement each other. Finally, suggestions are made to the school management and the education department to maintain the computer use as well as providing more computer training to the teachers.